How to Measure “Short-Term Hormonal Effects”? - Lothar A. J. Heinemann (Obstetrics and Gynecology International)
Background. Interest to assess short-term benefits or risks of sex-steroid hormone use (OC or HRT) exists for years. However, no validated scale is available to evaluate the broad array of described effects of short-term hormone use. Methods. A raw scale consisting of 43 specific items and 47 general data was developed. Surveys in Italy, Germany and Austria were performed and data analyzed by factorial analyses. The resulting new scale with 15 items underwent reliability and validity investigations. Results. The new scale consists of 15 items in 5 domains. Internal consistency reliability coefficients were satisfactory as were test-retest reliability coefficients. Content and concurrent validity were promising. Conclusion. Psychometric properties of the new scale suggest good characteristics to measure short-term effects of sex-steroid hormones in women. The scale seems to be appropriate, feasible, interpretable, reliable, and valid for their application as PRO scale.